The Creation of Students’ Academic Slang Expressions in the University of Botswana - Arua, Arua E.; Alimi, Modupe M. (Linguistik Online, 2009)
This study investigates the creation of students’ academic slang expressions at the University of Botswana with data obtained from 32 items in a questionnaire consisting of 89 items. The semantic process of extension is the most widespread creative process, producing 101 (66%) out of 153 selected slang expressions. Five morphological processes, compounding, derivation, conversion, acronymy and reduplication, together produce the remaining 52 (34%) expressions. Also the process of semantic extension features in all aspects of the students’ academic life in contrast with the other five morphological processes which are restricted. These findings show that the students draw extensively on and exploit the language resources at their disposal to create new meanings for describing their academic life. The findings also show that all the word formation processes highlighted relate to certain areas of the students’ academic life, notably, the students’ relationships with their lecturers, difficult courses and those who teach them, performances and grades.